O papel dos marcadores de angiogênese no feocromocitoma - Vargas, Carla Vaz Ferreira (2013)
Medullary thyroid carcinoma (MTC) is a rare malignant tumor originating from thyroid parafollicular C cells. This tumor accounts for 3-4% of thyroid gland neoplasias. MTC may occur sporadically or inherited. The hereditary MTC is part of syndromes of multiple endocrine neoplasia (MEN) 2A and 2B, familial medullary thyroid carcinoma (FMTC). Germline mutations of the RET (REarranged during Transfection) protooncogene cause hereditary form of cancer, whereas somatic mutations can be present in sporadic form of the disease. The RET gene encodes a receptor tyrosine kinase involved in the activation of intracellular signaling pathways leading to proliferation, growth, differentiation, migration and survival. Nowadays, the only possibility of cure for MTC patients consists of total thyroidectomy associated with lymph node dissection. Based on the knowledge of the pathogenic mechanisms of MTC, new drugs have been developed in attempt to control metastatic disease. Of these, the small-molecule tyrosine kinase inhibitors (TKIs) represent one of the most promising agents for MTC treatment and clinical trials have shown encouraging results. Hopefully, the cumulative knowledge about the targets of action of these drugs as well as TKI-associated side effects will help on choosing the best therapeutic approach in order to enhance its benefits.